Ketika Liturgi Bergerak: Mengalami Transformasi Iman melalui Bahasa Tubuh: When the Liturgy Moves: Experiencing Faith Transformation Through Body Language - Casandro Siregar (MURAI: Jurnal Papua Teologi Konstekstual, 2026)
This article examines Christian liturgy as an embodied event of faith by positioning the human body as a locus theologicus in which faith is experienced, expressed, and formed. Liturgy is not understood merely as a sequence of verbal texts and prayers, but as a symbolic action that involves gestures, postures, processions, and the active bodily participation of the worshipping community. Employing a theological-liturgical approach and engaging contemporary liturgical theology, this study analyzes the concept of participatio actuosa and the principle of lex orandi, lex credendi, lex vivendi within the liturgical practices of the Catholic Church and the Huria Kristen Batak Protestan (HKBP). The findings indicate that conscious and reflective bodily participation in liturgy plays a crucial role in shaping the communal identity of believers as the Body of Christ and possesses a transformative dimension that extends beyond the liturgical space. A “moving” liturgy forms a habitus of faith manifested in ethical attitudes, social solidarity, and everyday Christian praxis. However, this article also identifies a gap between the theological ideals of liturgy and contemporary ecclesial practice, where liturgical gestures are often performed mechanically without sufficient theological awareness. Therefore, the study underscores the importance of liturgical formation that emphasizes bodily awareness as a medium of faith, so that liturgy may truly function as a space of spiritual and social transformation.